Capacited Vehicle Routing Problem with CO2 Emission Minimization Considering Path Slopes - Cantão, L. A. P. [UNESP]; Yamakami, A.; Cantão, R. F. (Sociedade Brasileira de Matemática Aplicada e Computacional - SBMAC, 2022)
This work presents the application of a CO2 emission estimation function for cargo vehicles on a Capacited Vehicle Routing Problems (CVRP) setting, considering route’s slopes variation. Comparisons were established with functions minimizing fuel consumption and route length in a case study about selective collection of recyclable waste at Sorocaba, state of São Paulo, Brazil. Routes with lower emissions have been achieved without significantly increasing fuel consumption or distance traveled.
Keywords: CO2 emission; vehicle routing problem; path slope